Bioassesment of Batang Air Dingin Water Quality by using Macrozoobenthos in Koto Tangah District, Padang City - Risda Afifi Nasution; Nofrita Nofrita; Eggy Triana Putri; Izmiarti Izmiarti (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2020)
This study aims to determine the composition and structure of the macrozoobenthos community in Batang Air Dingin and water quality based on BMWP ASPT. This study used a survey method in determining the station by purposive sampling, based on typhical environmental condition along the river. Macrozoobenthos samples was collected by using surber net 30x30 cm2. The result showed the community in the form of Gastropods 6 genera, Insecta 26 genera, Oligochaeta 1 genus, and Hirudinea 1 genus. Total density of macrozoobenthos in the Batang Air Dingin river was 1182,22ind/m2 ranging from 180,00 ind/m2 to 402,22 ind/m2 with the highest density was found in the first station and the lowest at station four. The predominant type found at each station is different, station I is Elophyla, Neopherla, Hydropsyche; station II Eukifferiella, Polypedilum, Elophyla, Hydropsyche; station III Clithon, Eukifferiella, Polypedilum, Orthocladius; station IV Clithonand Thiara. The diversity of macrozoobenthos in Batang Air Dingin river range between 1,95-2,51 is classified as moderate with even distribution (E=0,84) range between 0,81-0,89. Batang Air Dingin water quality using BMWP ASPT from upstream to downstream range between 6,12 – 3,5. Classified unpolluted to heavily polluted.